가속화 저장 중 자포니카 및 통일형 현미의 산화 안정성 - 양진우(Jinwoo Yang); 이하나(Hana Lee); 곽지은(Jieun Kwak); 김영화(Younghwa Kim); 정헌상(Heon Sang Jeong); 이준수(Junsoo Lee) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2019)
본 연구는 현미의 생태형에 따른 산화 안정성 및 비타민 E와의 연관성에 대하여 가속화 저장을 통해 알아보고자 하였다. 가속화 조건에서 현미의 산패지표가 빠르게 증가하는 것을 알 수 있었으며, 이러한 산패지표의 증가는 생태형에 따라 차이를 나타내는 것을 알 수 있었다. 통일 계열의 과산화물가는 초기에 9.0~16.4 meq/kg, 자포니카 계열은 16.7~ 21.2 meq/kg을 나타내었다. 가속화 저장 후 통일 계열은 24.3~25.5 meq/kg, 자포니카 계열은 43.8~63.2 meq/kg을 나타내었다. 공액이중산가도 통일 계열이 자포니카 계열보다 높은 안정성을 나타내었다. 비타민 E 함량과 산패지표 간의 상관관계를 분석한 결과, α-토코페롤과 λ-토코페롤의 경우 모든 지질의 산패지표에 있어서 유의적인 음의 상관관계를 나타내었다. 통일형에서 높은 함량을 나타낸 λ-토코트리에놀의 경우 공액이중산가에서 매우 높은 음의 상관관계를 나타내었다. 따라서 현미의 저장에 있어서 비타민 E의 조성과 함량이 저장 안정성에 중요하게 작용하는 것을 알 수 있었다. 통일형은 자포니카형과 비교하여 높은 λ-토코트리에놀 함량을 갖는 차이점을 보였는데, 이러한 함량의 차이가 통일형의 높은 지질 산패 안정성에 영향을 미치는 것으로 생각된다. The purpose of this study was to investigate the oxidative stabilities and changes in vitamin E contents of Japonica (Ilpum and Samguang) and Tongil (Dasan1 and Joongwon) types during 4 months of storage at room temperature and under accelerated conditions. After storage, peroxide (POV) and conjugated diene (CDV) values were elevated and those values were higher under accelerated conditions than at room temperature. In addition, those values were lower in Tongil type than in Japonica type, meaning Tongil type had higher storage stability. POVs increased to 16.7∼27.8 and 24.3∼25.5 meq/kg in Tongil type and 25.0∼47.5 and 43.8∼63.2 meq/kg in Japonica type, respectively, at room temperature and under accelerated conditions. CDV showed the same trends under both storage conditions. The contents of tocopherols and tocotrienols decreased with storage time. In the correlation analysis, α- and λ-tocopherols showed significant negative correlation with POV and CDV. Especially, λ-tocotrienol was highly correlated with CDV. These results show that the composition of vitamin E played a substantial role in the oxidative stability of brown rice during storage. In conclusion, tongil type showed better storage stability than Japonica type. KCI Citation Count: 2